Sejarah Sosial Reformasi Pendidikan Islam - Anang Romli (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
Abstract; This paper will describe the meaning of Islamic education reform, the real condition of Muslims, The outline of Islamic education reform. Along with changes in state configuration and political reforms in several Islamic countries that often occur in Islamic countries or countries with a majority Muslim population also have an impact on changes in educational formation where these changes occur. An inevitability is that where there is a change there are also challenges in the conditions of that change. In this case the Islamic State we mean there are two first terms, the Islamic State in the sense of a State whose principles and laws use Islamic teachings as sources. In the Middle Ages, Islam in a period of decline, Western hegemony almost occurred in all Muslim-majority countries. The Muslim community is starting to realize the situation they are facing. Especially the backwardness of Islam in developing outside the truth of revelation. Islamic countries were colonized by Europeans. Therefore, Muslims are forced to let go of the shackles and stranglehold of the west. With that, the Islamic community began to overhaul the pattern of thinking through educational institutions. Here, it is hoped that Muslims will start thinking about the independence of the nation, political culture and education